2019
DOI: 10.1136/gutjnl-2018-316975
|View full text |Cite
|
Sign up to set email alerts
|

TGR5-dependent hepatoprotection through the regulation of biliary epithelium barrier function

Abstract: ObjectiveWe explored the hypothesis that TGR5, the bile acid (BA) G-protein-coupled receptor highly expressed in biliary epithelial cells, protects the liver against BA overload through the regulation of biliary epithelium permeability.DesignExperiments were performed under basal and TGR5 agonist treatment. In vitro transepithelial electric resistance (TER) and FITC-dextran diffusion were measured in different cell lines. In vivo FITC-dextran was injected in the gallbladder (GB) lumen and traced in plasma. Tig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 47 publications
2
57
0
Order By: Relevance
“…We recently reported that TGR5-mediated BA signaling in the biliary epithelium strengthened paracellular barrier function, protecting the liver parenchyma against BA-induced injury during cholestasis [6]. The present study provides evidence that TGR5 contributes to build a more hydrophilic BA pool at least through targeting the GB compartment in the enterohepatic cycle, by modulating GB function (dilatation) (Supplementary Figure 12).…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…We recently reported that TGR5-mediated BA signaling in the biliary epithelium strengthened paracellular barrier function, protecting the liver parenchyma against BA-induced injury during cholestasis [6]. The present study provides evidence that TGR5 contributes to build a more hydrophilic BA pool at least through targeting the GB compartment in the enterohepatic cycle, by modulating GB function (dilatation) (Supplementary Figure 12).…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, we and others previously reported that TGR5-KO mice were more sensitive to BDL-or CA-enriched diet-induced liver injury [5,6,8]. We recently reported that TGR5-mediated signaling operated a control on the biliary epithelial barrier function, explaining at least in part why TGR5-KO mice were more prone to BA-induced parenchymal injury [6]. However, TGR5 impact on GB function and/or BA pool composition might also contribute to this phenotype.…”
Section: Tgr5-mediated Hepatoprotection Through Gbmentioning
confidence: 85%
See 3 more Smart Citations